The Art of Knowledge Exchange : A Primer for Government Officials and Development Practitioners - World Bank (Washington, DC, 2014)
In 2009, in the midst of the financial crisis, analysts were concerned that banks in Nepal were dangerously overexposed to inflated real estate and equity markets. Nepal's Central Bank (NRB) decided to evaluate its commercial banks, but needed outside expertise and assistance for stress-testing its banks and assessing the damages that could result from economic shocks. Standard International Monetary Fund (IMF) models for evaluating banks in developed economies, however, proved too complex and were unsuitable for the circumstances of a small developing country. Meanwhile, the State Bank of Pakistan (SBP) had been carrying out quarterly stress-testing of banks in Pakistan. Upon hearing about SBP's capabilities from the World Bank, NRB leadership was eager to learn how to apply Pakistan's regulatory analysis in Nepal. The World Bank facilitated and funded a knowledge exchange between the two central banks so that NRB staff could learn to use a simplified stress-testing, scenario-based model to evaluate the financial stability of Nepal's banks, develop regulations to maintain the stability of banking institutions, and establish contingency plans in the case of failure of a Nepalese bank. This story demonstrates the power of doing development differently. Nepal is very motivated to solve a pressing problem. It actively shops for a solution: the standard model is not suitable, but the Pakistani model is. Pakistan is eager to share its model with Nepal. Nepal adopts and adapts it, and it works.